The impact of Gamma Ray on DNA molecule - Anwar Qasim Ahmed; Ali Yahya Salman; Adhraa Baqir Hassan; Ali Abid Abojassim; Hussien Abid Ali Mraity; Hussien Abid Ali Mraity (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2020)
The aim of this review is to provide an overview concerning the effect of one type of ionization radiation (e.g. gamma ray) on DNA considering three axes. The first one considers defining gamma ray, sources of gamma ray and interaction of gamma ray with matters. The second axis focuses on the DNA in term of , while the third one clarify the health effects of the gamma ray with different doses on DNA of human cells. Focusing on the DAN molecule in this review because its importance in two sides. First, the DNA of the human cell is responsible of the function of the specific type of that cell of a given organ. Second, it is responsible of the transferring the gigantic information across new generations.